Strategi Komunikasi Politik PKS Jawa Barat Dalam Meningkatkan Perolehan Suara pada Pemilu 2019 - Ahmad Mustopa Kamal; Wawan Budi Darmawan; Leo Agustino (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to identify and analyze the political communication strategy of the Prosperous Justice Party in increasing the number of votes in the Electoral District of West Java VIII in the 2019 West Java DPRD Member Election. To answer this problem, an analysis of the main research questions was carried out, namely: the PKS political communication strategy. in increasing the number of votes in the 2019 elections. The approach used in this research is qualitative. In this study the informants were selected by purposive sampling (sample aims), namely: PKS Electoral District VIII Council, Chairperson of West Java PKS DPW, Chair of the West Java DPW PKS Election Team, Community Leaders of Bekasi City and Depok City, Chairperson of West Java PDIP DPD Election Team and Head of PPP Bekasi City, journalist. The results showed that, the communication strategy carried out by each cadre and legislative candidate who was nominated was building an inclusive self-image and eliminating the image of an exclusive party, eliminating stereotypes in society, building cooperation with all elements of the nation, and having a place in the hearts of the people. , as well as the strength of PKS party cadres with mutual help and high solidarity, they can help each other to campaign and reduce campaign costs